Forgone healthcare for medically vulnerable groups during the pandemic era: experiences of family caregivers of young adults with substance use disorders in Zambia - Kabembo, Ireen Manase (Frontiers in Public Health, 2024)
Introduction: Scholars worldwide have defined the COVID-19 pandemic as a mass-disabling event of our time. The situation is grave for families experiencing financial hurdles while caring for young adults in recovery from addiction problems.Using semi-structured interviews with 30 purposively selected family caregivers (FCGs) of young adults with substance use disorders (SUDs) in Lusaka, Zambia, this study reveals several factors influencing that made family caregivers forgone healthcare for this medically vulnerable group despite perceiving a need to utilize healthcare.Results: Among them were Ffinancial challenges and huge out-of-pocket bills; caregivers' perceived far-fetched recovery of the young adult; the cost of medication and transportation; the young adult's little perceived need for healthcare service use, their runaway and treatment elusive tendencies and their tendency to run away and desist from going to healthcare facilities; caregiver concerns about contracting the virus, and the stigma associated with it; and a fragmented child and adolescent mental health system influenced forgone healthcare., and a poor continuum of care. The young adults were often In most instances, the youth with SUDs ran away from home and were unavailable for days and months, posing challenges to the continuity of care. Despite caregivers' acknowledgment of the availability of healthcare professionals, young adults with problematic substance use had limited access to SUD recovery services, resulting in adverse health outcomes. Results also show that most family caregivers had huge out-of-pocket bills, which they had challenges financing. They encountered challenges in accessing and purchasing psychotropic medications, which were difficult to find during the lockdowns. Some family caregivers in formal employment lost their sources of income by being laid off from work due to the pandemic and skipping work to attend to caregiving responsibilities. Most of those in self-employment had to close their business and stay home to look after their youth. Several caregivers kept their youth at home because they failed to access private residential SUD recovery services. Family caregivers mostlyThey only relied on outpatient public Formatted: Strikethrough